Banks, stock market and economic growth in Botswana: a time series analysis - Malebye, Nthabiseng (Department of Finance and Tax, 2022)
This study examines the relationship between banks, stock market and economic development in Botswana using quarterly data from 1995 to 2016. To find out if there is a link between financial development and economic growth, the three measures of stock market development used are stock market capitalization, total value of shares traded and turnover. For bank-based financial development, the proxy is bank credit to private sector and the measure of economic growth is real gross domestic product (GDP) per capita. To analyse the long run and short run relationships among the variables of interest, this study implements the Autoregressive Distributed Lag (ARDL) cointegration technique and the Granger causality technique to find the direction of causality. The findings indicate that there is a positive short and long run relationship between stock market variables and economic growth when turnover and market capitalization are used as proxies and value traded is significant and negatively related to economic growth. The study found that bank credit to private sector is negatively related to economic growth both in the short and the long run. There is bidirectional causality between stock market financial development and economic growth and no causal relationship between banking financial development and economic growth in Botswana. This study recommends that there should be appropriate reforms to develop the financial sector in Botswana to help promote economic growth. Botswana should also have reforms to promote economic growth to foster stock market financial development. This study also offers a comprehensive and detailed overview of the state of the economy, banking system and the financial markets system of Botswana which can help foreign investors as well as individual and institutional investors in making sound investment decisions.